Can exercise regulate the relationship between noise pollution and the perception of physical and mental health among Chinese adults? An empirical study based on CGSS 2021 - Shi, Peng; Feng, Xiaosu; Lyu, Shanshan (Frontiers in Public Health, 2025)
ObjectiveTo explore the relationship between noise pollution, exercise, and the perception of physical and mental health among Chinese adults, to test the moderating effect of exercise on the relationship between noise pollution and physical and mental health perception, and to provide a basis for the formulation of environmental health policies and public health policies.MethodsUsing 2,717 data points from the 2021 China General Social Survey (CGSS), data analysis was conducted using SPSS 25.0, Stata 12.0 software, and GraphPad Prism 8 software. The Mann–Whitney U test, Kruskal-Wallis test, contingency table χ2 test, multiple linear regression analysis, binary Logistic regression analysis, and Generalized Linear Model (GLM) were employed.ResultsThe average age of the subjects was 52.04 ± 17.64 years, including 54.8% women. After controlling for related confounding factors, the high noise pollution perception group had lower perception of physical health (PPH; β = −0.135, 95%CI = -0.231 −0.039, p < 0.01) and perception of mental health (PMH; β = −0.151, 95%CI = −0.240 −0.062, p < 0.01). The regular exercise group had higher PPH (β = 0.224, 95%CI = 0.146 0.342, p < 0.01), PMH (β = 0.093, 95%CI = 0.001 0.184, p < 0.01), and perception of physical and mental health (PPMH; β = 0.236, 95%CI = 0.137 0.334, p < 0.01). Exercise has a significant moderating effect on the relationship between noise pollution and physical and mental health perception (p < 0.05), with regular exercisers generally having higher PPH, PMH, and PPMH.ConclusionThe high noise pollution perception group has lower physical and mental health perception; the regular exercise group has higher physical and mental health perception. Regular exercise can counteract the lower physical and mental health perception caused by higher noise pollution.